The development of the professionalism of adult educators: a biographical and learning perspective - Cornelia Maier-Gutheil; Christiane Hof (European Journal for Research on the Education and Learning of Adults, 2011)
To investigate the development of the professionalism of adult educators, we compareindividuals' narratives of their professional work at different times in their biographies.Using data from a qualitative longitudinal study, the paper includes two case studiesthrough which we show phases of learning in the development of professionalism. Wereconstruct forms and meanings of learning in this process. The study allows insightsinto differences in professional learning during the life course and the influence ofinstitutional and social context in the development of professionalism.